إدارة الصف في تعليم اللغة العربية في المدرسة الثانوية الإسلامية الحكومية باسوروان - Al Fikri, Siti Mashlahah; Al Fathiyah, Siti Fathimah (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2023)
Classroom management is a skill that must be possessed by every teacher, because in class management there are positive interactions that must be built by teachers and students during the learning process, therefore class management is a very important one that must be mastered by teachers. Classroom management activities for learning Arabic intend to create a stable and comfortable atmosphere and class conditions so that the teaching and learning process can take place effectively and efficiently. The purpose of this research is to reveal and analyze the classroom management in learning Arabic in the MAN Kota Pasuruan both in face-to-face and online learning activities. This research uses descriptive qualitative research. The data collection techniques used were interviews and observations. Data analysis was carried out through data collection schemes, condensation, display and verification as well as conclusions. The results of this study are that the implementation of learning is carried out in the classroom and outside the classroom, the class conditions allow for the learning process, learning is carried out using the 2013 curriculum. And also online learning activities using e-learning, WhatsApp groups, Youtube, and Zoom Meating. The implementation of learning in the classroom is carried out by instilling class discipline and providing rules that invite students to learn actively and the learning process is fun in the form of changing sitting positions with a specific purpose, while learning outside the classroom is carried out by habituating language practices and games.